New species of Chorizococcus McKenzie, 1960 and Spilococcus Ferris, 1950 (Hemiptera: Coccomorpha: Pseudococcidae) from India - Joshi, Sunil; Churi, Paresh; Amembal, Amit; Pai, Sachin G.; Deepthy, K.b. (Zootaxa, 2026)
Two new mealybug species (Hemiptera: Coccomorpha: Pseudococcidae) are described from India. The genus Spilococcus Ferris is recorded from India for the first time, with description and illustration of the new species, Spilococcus gullanae Joshi, Churi & Amembal, sp. nov., which is most similar to S. geraniae (Rau). Characters distinguishing S. gullanae from the other Spilococcus species recorded from the same host family in the same geographical area are discussed. A second new species is described and illustrated in the closely related genus, Chorizococcus McKenzie: C. watsonae Joshi, Pai & Deepthy, sp. nov. A key is provided to separate the adult females of Chorizococcus occurring in the Oriental region.